SLC38A10 Knockout Mice Display a Decreased Body Weight and an Increased Risk-Taking Behavior in the Open Field Test - Lindberg, Frida A.; Nordenankar, Karin; Fredriksson, Robert (Frontiers in Behavioral Neuroscience, 2022)
The solute carrier 38 family (SLC38) is a family of 11 members. The most common substrate among these are alanine and glutamine, and members are present in a wide range of tissues with important functions for several biological processes, such as liver and brain function. Some of these transporters are better characterized than others and, in this paper, a behavioural characterization of SLC38A10-/- mice was carried out. A battery of tests for general activity, emotionality, motor function and spatial memory was used. Among these tests, the elevated plus maze, Y-maze, marble burying and challenging beam walk have not been tested on the SLC38A10-/- mice previously, while the open field and the rotarod tests have been performed by the International Mouse Phenotyping Consortium (IMPC). The results from this study, unlike the results from IMPC, showed that SLC38A10-/- mice spend less time in the wall zone in the open field test than WT mice, implying that SLC38A10 deficient mice have an increased explorative behavior, which suggests an important function of SLC38A10 in brain. The present study also confirmed IMPC’s data regarding rotarod performance and weight, showing that SLC38A10-/- mice do not have an affected motor coordination impairment and have a lower body weight than both SLC38A10+/- and SLC38A10+/+ mice. These results imply that a complete deficiency of the SLC38A10 protein might affect body weight homeostasis, but the underlying mechanisms needs to be studied further.